What works for you. (2nd February 2021) - Caswell, Jo
Abstract : Jo Caswell provides a practical guide to how the whole staff team, including trainees, can benefit from a strong understanding of the Early Years Inspection Handbook and use it to identify their own development areas. Storing records in an efficient and accessible way is a good place to start.